The Social Construction of Muslim Women’s Careers in the United Kingdom - Lehmann, Nicole (2016)
Recent conceptual career developments have been arguing for the emergence of ‘new careers’ due to a weakening of the organizational bond leading to a greater emphasis on the agency of the career actor. Muslim women in particular are at the interaction of several forces, such as culture, family, society, economy as well as their own perceptions and values, which questions the extent of individual choice within those socioeconomic constraints. Through qualitative in depth-life history interviews, eight women in various employment relations were asked to narrate on the perception of their careers, especially with regards to being a Muslim woman. The analysis, following a social constructionist framework, revealed how the Muslim women’s careers were significantly influenced by family and social relations, institutional and economic forces as well their own faith, values and priorities. Furthermore, the subjective perception of their careers emphasized the importance of meaning at work over status and financial incentives as well as the social and interrelational aspects of work. Hence, this study highlights the significance of researching the experiences of minorities as well as those in less privileged positions in order to better account for the larger segments of the current workforces and thereby questions the applicability of current career theories.